A Study of Conversational Implicature in the Old Man and the Sea Novel Written by Ernest Hemingway - Muhammad Qordawi; Rugaiyah (DISCOVERY JOURNAL, 2022)
The purposes of this research are (1) to find the kinds of conversational implicature; (2) to find the purposes of the conversational implicature found in The Old Man and The Sea Novel Written by Ernest Hemingway. This research was designed as qualitative research. The data were collected from the old man and the sea novel. The researcher obtained the data by reading it first, reading all the novel and understand the story. Second, categorizing the conversational implicature from the conversation in the novel. Third, analyzing the conversation and find the purposes of conversational implicature. In the data analysis, the researcher applied interactive qualitative method by (Sugiono, 2017:252) and pragmatic identity method by Hieronimus Canggung Darong (2020). Additionally, the researcher gave more explanation on the discussion part to give more dependability on the data. The result of the research shows There are two types of conversation implications. They are generalized conversational implications and specific conversational implications. But the implications of conversation are to provide and entertain information, self-defense, power, and etiquette. In summary, generalized conversational implications often occur in dialogue between main character.